Breve síntesis sobre la introducción de nuevo armamento en Egipto durante la dinastía XVIII - Martínez Babón, Javier (Espacio Tiempo y Forma. Serie II, Historia Antigua, 2001)
The traditional Egyptology emphasises that new weapons were introduced in Egypt during the Hyksos Period. If we studied the sources, we could conclude that, in their last phase, the Hyksos introduced horses and chariots, swords and daggers with inlaid handles, and composite bows. Other weapons, traditionally associated to the Hyksos, like armours, helmets and sickieswords, arrived to Egypt during the first phase of the XVIIIth Dynasty, when Egypt conquered the territories of Syría-Palestine. In spite of the new technology, the Egyptian Army kept on using weapons of great tradition, as the axe.